The Motor Function Evaluation of College Students’ Physical Activity State From the Perspective of Educational Psychology - Ge, Sha; Song, Chao; Yao, Wanxiang (Frontiers in Psychology, 2021)
College students have taken part in less and less physical activities as a result of the common static lifestyle in recent years, lowering the level of motor function. This phenomenon has been highly concerned by schools and the government, and it is necessary to take corresponding measures to change it. The general motor function level of Chinese college students is explored first based on artificial intelligence and the human-computer interaction technology. The Physical Activity Questionnaire for College Students is compiled by referring to the International Physical Activity Questionnaire, and 561 students from colleges in Tianjin province are assessed based on functional movement screen (FMS). Spearman correlation and multivariate regression analysis (MRA) are used to analyze the correlation between the motor function and physical activity status. In terms of the lunch break frequency, the proportion of students having 1-2 times lunch breaks in a week is the highest (54.15%); in terms of the frequency of doing moderate physical exercise, the proportion of students doing moderate physical exercise for 1-2-day(s) in a week is the highest (50.61%); in terms of the frequency of doing heavy physical exercise, the proportion of students doing heavy exercise for 1-2-day(s) in a week is the highest (47.26%); in terms of the sedentary time, the proportion of students with sedentary time more than 5 hours in a day is the highest (40.61%); in terms of eye-use time, the proportion of students with 8-10-hours eye use time in a day is the highest (43.61%). Besides, in terms of the FMS score, the proportion of students with 13-15 FMS is the highest (48.46%). The hurdle step (21.03%), straight knee lift (22.52%), and body rotation stability (18.31%) have a relatively low proportion among the 3-point items. There is a positive correlation between motor function score with the time of moderate exercise and the time of heavy exercise (P<0.05). College students generally have insufficient rest time, long eye-use time, and long sitting time, leading to a low level of motor function, manifested by an asymmetry between both sides of the body and poor trunk stability.